Fisiese, seksuele en emosionele kindermishandeling en- verwaarlosing : 'n argiefstudie - Bruwer, Jeanne-Lu (Jeanne Catherine Louise) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- University of Stellenbosch, 2007.